Agamemnon in performance 458 BC to AD 2004 - Macintosh, Fiona, 1959- (OUP E-Books., 2005)
This interdisciplinary, multi-author volume is devoted to the performance reception of Aeschylus's Agamemnon, the first play in his Oresteia trilogy. The eighteen essays trace the story of the impact and influence of this seminal play, from its original performance in classical Athens, through ancient Rome and the European Renaissance until the present day. Genres discussed include film, the novel, and lyric poetry as well as theatre and opera. The volume is fully. illustrated, and includes an extensive bibliography and chronological appendix. - ;Aeschylus' Agamemnon, the first play in the Ore.